2021
DOI: 10.7753/ijsea1004.1001
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pine Tree Sawdust on the Volume Compressibility of Expansive Soils

Abstract: Expansive soils are very important natural geological materials used in the geotechnical applications in the worldwide. After compacting, they are used as hydraulic barriers in earth structures, such as core of earth fill dams, landfill liners, and etc. However, these soils have some defects from technical points of view. To remove the defects, one of the soil improvement methods is mixing of these soils with granular materials. In this study, pine tree sawdust was used as granular additive material to stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In Turkey, research carried out on the application of pine sawdust powder passing the No. 4 sieve in Erzurum region soil showed a decrease in the MDD and an increase in the OMC and strength of unconfined compression with the increase in the percentage of sawdust added [1,108,109]; additionally, research carried out adding 1 to 5% of sawdust powder passing No. 20 sieve in Istanbul fine soil showed the strength to unconfined compression increased with an increase in the percentage of sawdust added, showing optima of 3% and 2% respectively.…”
Section: Sawdust Powdermentioning
confidence: 95%
See 1 more Smart Citation
“…In Turkey, research carried out on the application of pine sawdust powder passing the No. 4 sieve in Erzurum region soil showed a decrease in the MDD and an increase in the OMC and strength of unconfined compression with the increase in the percentage of sawdust added [1,108,109]; additionally, research carried out adding 1 to 5% of sawdust powder passing No. 20 sieve in Istanbul fine soil showed the strength to unconfined compression increased with an increase in the percentage of sawdust added, showing optima of 3% and 2% respectively.…”
Section: Sawdust Powdermentioning
confidence: 95%
“…200). Regarding the investigations that used powder sawdust [1,8,36,48,72,78,[108][109][110], it was observed that these were screened with sieves of openings between 4.75 mm and 0.42 mm (Sieve No. 4 and Sieve No.…”
Section: Fiber Length and Sizementioning
confidence: 99%
“…In Turkey, research carried out on the application of pine sawdust powder passing the No. 4 sieve in Erzurum region soil showed a decrease in the MDD and an increase in the OMC and strength of unconfined compression with the increase in the percentage of sawdust added [1,108,109]; additionally, research carried out adding 1 to 5% of sawdust powder passing No. 20 sieve in Istanbul fine soil showed the strength to unconfined compression increased with the increase in the percentage of sawdust added, showing optima of 3% and 2% respectively, permeability also increased with the increase in the percentage of sawdust added, while the PI, MDD, and OMC decreased.…”
Section: Sawdust Powdermentioning
confidence: 96%
“…200). Regarding the investigations that used powder sawdust [1,8,36,48,72,95,[108][109][110], it was observed that these were screened with sieves of openings between 4.75mm and 0.42mm (Sieve No. 4 and Sieve No.…”
Section: Fiber Length and Sizementioning
confidence: 99%
“…A study on the effects of pine sawdust on the volumetric compressibility of an expansive soil showed that the volumetric compressibility coefficient of the tested soil decreased significantly with the addition of a higher pine sawdust content; on the other hand, the consolidation coefficient of the tested soil increases [65].…”
Section: Sawdustmentioning
confidence: 99%